Pheophorbide A-Mediated Photodynamic Therapy Potentiates Checkpoint Blockade Therapy of Tumor with Low PD-L1 Expression - Qinli Tong; Jiaojiao Xu; Aihua Wu; Chen Zhang; Afeng Yang; Sihang Zhang; Hongzheng Lin; Wei Lu (MDPI AG, 2022)
Although the immune checkpoint blockade (ICB) has made a great success in cancer immunotherapy, the overall response rate to the ICB, such as anti-programmed death ligand 1 (PD-L1) therapy, remains only at 20-30%. One major reason is the low expression level of the immune checkpoint in a certain type of tumor cells and its insufficient activation of the host immune system. Herein, we reported a cyclic RGD (cRGD)-modified liposomal delivery system loading the anti-PD-L1 antibody and the photosensitizer pheophorbide A (Pa), allowing a targeting of the low PD-L1 expressing 4T1 mouse breast cancer cells through the recognition of an overexpression of αvβ3 integrin on the tumor cells. The Pa-mediated photodynamic therapy (PDT) elevated the expression of PD-L1 on the tumor cells. PDT, in combination with the anti-PD-L1 therapy, promoted the activation and maturation of dendritic cells as well as the infiltration of cytotoxic T lymphocytes, resulting in the augmented antitumor immune response for the enhanced therapeutic effect. These results demonstrated the combined therapeutic effects of PDT and ICB on the tumor with low PD-L1 levels. Our study suggested that an increase in the PD-L1 expression in tumor cells by PDT would be a promising adjuvant treatment to overcome the ICB irresponsiveness.